Earliness and morphotypes of common wheat cultivars of Western and Eastern Siberia - S. E. Smolenskaya; V. M. Efimov; Y. V. Kruchinina; B. F. Nemtsev; G. Y. Chepurnov; E. S. Ovchinnikova; I. A. Belan; E. V. Zuev; Chenxi Zhou; V. V. Piskarev; N. P. Goncharov (Вавиловский журнал генетики и селекции)
The global and local climate changes determine the producing of highly-adaptive common (bread) wheat commercial cultivars of a new generation whose optimal earliness matches the climatic features of the territory where the cultivars are farmed. Principal component analysis involving our own and published data has been applied to investigate 98 commercial common wheat cultivars from Western and Eastern Siberia comparing their morphotypes; cultivar zoning time; length of the vegetation period; 1000-grain weight, and inheritance of spring growth habit. It demonstrated that the dominant Vrn gene polymorphism determining the spring growth habit of the Siberian cultivars was minimally polymorphic. In 75 % of the tested cultivars, the spring growth habit was controlled by digenic, namely dominant Vrn-A1 and Vrn-B1 genes. In 25 % of them (24 cultivars), spring growth habit is controlled by a single gene. In 19 and 5 of these cultivars spring growth habit is controlled by only one dominant gene, Vrn-B1 or Vrn-A1, respectively. In cv. Tulun 15, a trigenic control was identified. A conclusion about the optimality of the digenic control for the climatic conditions of both Western and Eastern Siberia has been confirmed. However, since none of the tested cultivars had the dominant Vrn-D1 gene typical of the regions of China and Central Asia bordering Siberia, it can be considered as an additional argument in favor of the European origin of Siberian common wheat cultivars. The revealed high frequency of the Vrn-B1c allele in the Western Siberian cultivars and the Vrn-B1a allele in the Eastern Siberian cultivars suggests their selectivity. The analysis also confirmed the dominance of red glume (ferrugineum, milturum) and awned spike (ferrugineum, erythrospermum) varieties in the Eastern Siberian cultivars, and white glume and awnedless spike (lutescens and albidum) ones in the Western Siberian cultivars. Small grain size cultivars are more typical of Eastern than Western Siberia. The retrospective analysis based on the cultivars’ zoning time included in the “State Register for Selection Achievements Admitted for Usage” brought us to the conclusion that the earliness/lateness of modern Siberian commercial cultivars was not regionally but rather zonally-associated (taiga, subtaiga, forest-steppe and steppe zones).